Stimulasi Tumbuh Kembang Melalui Pijat Bayi di RT 05 RW 05 Kecamatan Langensari Tahun 2022 - Intan Pratiwi; Luvi Dian Afriyani; Sofaniah Nurrahmi; Restyany Novyarsy Pasombo (Universitas Ngudi Waluyo, 2022)
Growth and development in infants cannot be separated from the concept of growth and development. Growth is a physical change and an increase in the size of the body parts of an individual, each of which is different, while development is the improvement in more complex abilities, skills, and body functions in gross motor skills, fine motor skills, speech and language, as well as socialization and independence that is needed. possessed by individuals to adapt to the environment Every child needs to get regular stimulation as early as possible and continuously at every opportunity. Stimulation of child growth and development is carried out by mothers and fathers who are the closest people to children, substitute mothers/caregivers, other family members and community groups in their respective households and in daily life. Lack of stimulation can cause deviations in child development and even permanent disorders. One form of stimulation that has been carried out by the community is baby massage. used in conducting community service in RT 05 RW 05 Langensari District is situation analysis. The subjects in this community service are mothers who have children aged 0-5 years and use pre and post test designs. The subjects in this community service are mothers who have children aged 0-5 years. Data analysis was carried out univariately, univariate analysis described each variable by displaying the percentage of each variable .material was given about stimulation of growth and development through baby massage, then asked questions to the counseling participants. evaluation of the counseling that has been given by mothers and cadres can apply massage for healthy babies and toddlers at home.. AbstrakTumbuh kembang pada bayi tidak terlepas dari konsep pertumbuhan dan perkembangan. Pertumbuhan adalah perubahan fisik dan peningkatan ukuran bagian tubuh dari seseorang individu yang masing-masing berbeda, sedangkan perkembangan adalah bertambah sempurnanya kemampuan, keterampilan, dan fungsi tubuh yang lebih kompleks dalam kemampuan motorik kasar, motorik halus, bicara dan bahasa, serta sosialisasi dan kemandirian yang dimiliki individu untuk beradaptasi dengan lingkungan Setiap anak perlu mendapat stimulasi rutin sedini mungkin dan terus menerus pada setiap kesempatan. Stimulasi tumbuh kembang anak dilakukan oleh ibu dan ayah yang merupakan orang terdekat dengan anak, pengganti ibu/pengasuh anak, anggota keluarga lain dan kelompok masyarakat di Lingkungan rumah tangga masing-masing dan dalam kehidupan sehari-hari. Kurangnya stimulasi dapat menyebabkan penyimpangan tumbuh kembang anak bahkan gangguan yang menetap. Salah satu bentuk stimulasi yang selama ini dilakukan masyarakat adalah dengan pijat bayi yang digunakan dalam melakukan pengabdian masyarakat di RT 05 RW 05 Kecamatan Langensari adalah analisa situasi. Subyek dalam pengabdian masyarakat ini adalah ibu yang memiliki anak usida 0-5 tahun dan menggunakan desain pre and post test. Subyek dalam pengabdian masyarakat ini adalah ibu yang memiliki anak usida 0-5 tahun. Analisis data dilakukan secara univariat, analisis univariat mendeskripsikan setiap variabel dengan menampilkan persentase masing-masing variabel. ibu yang mempunyai bayi balita dan kader, diberikan materi tentang stimulasi tumbuh kembang melalui pijat bayi, lalu dilakukan tanya jawab pada peserta penyuluhan. evaluasi dari penyuluhan yang di berikan ibu dan kader dapat menerapkan pijat bayi dan balita sehat di rumah.